Role of Accessibility in Development and Functioning of Settlements - Szörényiné Kukorelli, Irén (Discussion Papers, 1990)
The economic structure, development ability, and functioning of settlements in a region are significantly influenced by the measure of connections of settlements of various importance. Transportation network is a growth factor playing an important role in the life of settlements. The connection of large settlements to each other and to less important settlements in their gravity zones is closely related to the development and functioning of the settlements. This paper intends to analyze the connection system of settlements with the concept of transportation accessibility. Only mass transportation is included in the analysis. Accessibility has two distinctive sides: the first is physical or spatial dimension, which mostly belongs to transportation geography, the other side is social dimension, which is closest to sociology. The author examines the accessibility among centres and that between centres and the settlements in their gravity zones by measuring the physical side. The accessibility studies were carried out according to settlement network hierarchy.